Design and construction risks in BOT type mega transportation projects - Aladag, Hande; Isik, Zeynep (EMERALD GROUP PUBLISHING LTD, 2019)
Purpose In build-operate-transfer (BOT) transportation projects, design and construction phases are critical in terms of their effect on time and cost overruns. The purpose of this paper is to identify the role of risk factors affecting these phases and their significance level for BOT transportation projects. Design/methodology/approach Design and construction risks were determined and then validated by focus group discussions. Afterwards, an illustrated case study was presented to better understand the effects of determined risks in a BOT mega transportation project. As the last step of the study, the fuzzy analytical hierarchy process method was used to prioritize risk factors. Findings The prominent risk factors were found out as occupational accidents, integration between design and construction phases and excessive design variations. Originality/value Though the risk management of BOT projects has been investigated frequently in the literature, there is a knowledge gap in the quantitative evaluation of risk significance specific to design and construction risks. The prioritization of determined risks with an associated case from a mega transportation project will contribute to the BOT project practitioners about possible challenges in design and construction phases in BOT mega transportation projects.
Keywords: Design; Risk management; Project management; Construction; PUBLIC-PRIVATE PARTNERSHIP; ANALYTIC NETWORK PROCESS; ALLOCATION; SUCCESS; Engineering; Business & Economics